Persepsi Stakeholder terhadap Inovasi Digital dalam Jasa Keagenan Kapal di Pelabuhan Batam - Samiyono Samiyono; Agung Kwartama; Paiman Paiman; Desiana Endah Pramesti; Sumiyatiningsih Sumiyatiningsih; Akhmad Sopani (Dharma Ekonomi, 2024)
Digital innovation has become a crucial catalyst for the transformation of the ship agency services sector, particularly within the Port of Batam. This paper seeks to examine the perceptions of diverse stakeholders, including shipping agents, vessel owners, and local authorities, regarding the integration of digital innovations into ship agency services. Employing a combination of qualitative and quantitative methodologies, this research collects data through surveys and in-depth interviews with pertinent stakeholders. The results reveal that although challenges exist in the adoption of technology, a substantial majority of stakeholders acknowledge the considerable advantages of digital innovation, such as enhanced operational efficiency, improved transparency, and cost reduction. This study aims to provide insightful perspectives for policymakers and industry professionals in crafting more effective strategies for the deployment of digital innovation in the ship agency domain.